Supercritical Fluid Chromatography – Theoretical Background and Applications on Natural Products - Hartmann, Anja; Ganzera, Markus (Planta Medica, 2015)
The use of supercritical fluid chromatography for natural product analysis as well as underlying theoretical mechanisms and instrumental requirements are summarized in this review. A short introduction focusing on the historical development of this interesting separation technique is followed by remarks on the current instrumental design, also describing possible detection modes and useable stationary phases. The overview on relevant applications is grouped based on their basic intention, may it be (semi)preparative or purely analytical. They indicate that supercritical fluid chromatography is still primarily considered for the analysis of nonpolar analytes like carotenoids, fatty acids, or terpenes. The low polarity of supercritical carbon dioxide, which is used with modifiers almost exclusively as a mobile phase today, combined with high efficiency and fast separations might explain the popularity of supercritical fluid chromatography for the analysis of these compounds. Yet, it has been shown that more polar natural products (e.g., xanthones, flavonoids, alkaloids) are separable too, with the same (if not superior) selectivity and reproducibility than established approaches like HPLC or GC.
Keywords: SFC; supercritical fluid chromatography; natural products analysis; preparative; analytical; applications